Stepwise Glucoheptoamidation of Poly(Amidoamine) Dendrimer G3 to Tune Physicochemical Properties of the Potential Drug Carrier: In Vitro Tests for Cytisine Conjugates - Anna Czerniecka-Kubicka; Piotr Tutka; Marek Pyda; Małgorzata Walczak; Łukasz Uram; Maria Misiorek; Ewelina Chmiel; Stanisław Wołowiec (Pharmaceutics, 2020)
Third-generation poly(amidoamine) dendrimer (PAMAM) was modified by stepwise primary amine group amidation with d-glucoheptono-1,4-lactone. The physicochemical properties of the conjugates—size, ζ potential in lysosomal pH 5 and in neutral aqueous solutions, as well as intramolecular dynamics by differential scanning calorimetry—were determined. Internalization and toxicity of the conjugates against normal human fibroblasts BJ were monitored in vitro in order to select an appropriate carrier for a drug delivery system. It was found that initial glucoheptoamidation (up to 1/3 of amine groups of neat dendrimers available) resulted in increase of conjugate size and ζ potential. Native or low substituted dendrimer conjugates accumulated efficiently in fibroblast cells at nontoxic 1 µM concentration. Further substitution of dendrimer caused consistent decrease of size and ζ potential, cell accumulation, and toxicity. All dendrimers are amorphous at 36.6 °C as determined by differential scanning calorimetry (DSC). The optimized dendrimer, half-filled with glucoheptoamide substituents, was applied as carrier bearing two covalently attached cytisine molecules: a rigid and hydrophobic alkaloid. The conjugate with 2 cytisine and 16 glucoheptoamide substituents showed fast accumulation and no toxicity up to 200 µM concentration. The half-glucoheptoamidated PAMAM dendrimer was selected as a promising anticancer drug carrier for further applications.